PENGARUH KADAR AIR, NaCl DAN JUMLAH PASSING TERHADAP KARAKTERISTIK REOLOGI MI JAGUNG [The Effect of Moisture, NaCl and Number of Passing on Corn Noodle Rheological Properties] - Tjahja Muhandri; Subarna Subarna (Jurnal Teknologi dan Industri Pangan, 2009)
The objective of this research was to investigate the effect of moisture (70, 75 and 80% v/w), NaCl ((0, 1, 3%) and number of passing (1, 2 and 3 times) on the properties of the corn noodle.  The 100 mesh of corn flour of P21 variety and scientific laboratory single screw extruder were used. Cooking loss decreased with the increase of moisture and NaCl.  Hardness decreased with the increase of moisture, NaCl and passing.  Cohesiveness, tensile strength and elongation increased with the increase of moisture, NaCl and  number of passing.